The role of tumor necrosis factor (TNF-alpha) in therapy of malignant diseases - Wcisło, Gabriel; Korniluk, Jan; Szarlej-Wcisło, Katarzyna; Nurzyński, Paweł; Duchnowska, Renata; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Tumor necrosis factor-alpha (TNF-alpha) is a pleiotropic and proinflamatory cytokine with anticancer cytotoxic activity. Although enthusiasm has gone mostly upon the systemic and locoregional therapy with the exception of isolated perfusion. Clinical trials showed that TNF-alpha had high grade toxicity profile with very narrow therapeutic window. The toxicity profile is expressed by: hypotension - 92%, hepatotoxicity - 42%, fever and chills - 17%. The summary of clinical trials with TNF-alpha systemic therapy shows that the response rate extent is between 2 to 4%. Moreover, additional clinical trials with TNF-alpha injected to tumors or infused intrapleurally, intraabdominally, and intravesically have been dissapointing because of low response rate. Most studies have been focused on the toxicity profile and safety of such therapy. Unfortunately, responses have been noted incidentally. Another chance, and by the way, challenge appears with isolated perfusion. Primary results have been encouraging with high response rate in patient with in-transit melanoma and sarcoma. In case of in-transit melanoma the response rate reached 90% objective responses, and in patients with sarcoma 75%. Presented data suggest that more achievement is necessary to define a role of TNF-alpha in the therapy of limb tumors. Just novel indication, appears, namely hepatic isolation perfusion. The regimen, consisiting of TNF-alpha and melphalan given as isolated perfusion, appears to be effective in patients with metastases confined to the liver. Although, the mortality rate heve rather been high up to 33%, the latest results are very encouraging. This regimen is responsible for 75% overall response rate in such patients. The technological progress allowed to bring this procedure safer and not to brink on the edge of life and death, as it was in the begining of the trials. For sure, the isolated perfusion is not easy to work with. This reviw is about to shed light on the role of TNF-alpha in the therapy of cancer patients.